PENINGKATAN LITERASI DIGITAL DAN LOGIKA PEMROGRAMAN C++ MELALUI PENDEKATAN GAME-BASED LEARNING MENGGUNAKAN CODECOMBAT DI SMK BAKTI PURWOKERTO - Arif Ginanjar; Septiara Janatun Gresela; Gunawan Pamuji; Diva Rahma Listyaningrum (CV. Denasya Smart Publisher, 2026)
Digital literacy and programming logic are essential competencies for vocational high school students to face future industrial challenges. This community service activity aims to improve these competencies through a C++ programming workshop using the CodeCombat game-based learning platform at SMK Bakti Purwokerto. The implementation method applies an educational approach that includes interactive theoretical explanations with hands-on practice in the laboratory, facilitating students to master basic logic structures such as variables, input-output, and loops visually. The results of the activity showed a significant positive impact, where 98% of participants successfully completed the game's basic level challenges independently and demonstrated a significant increase in technical understanding. Furthermore, the integration of gamification was proven effective in increasing student enthusiasm and active participation in completing coding missions. It was concluded that this approach provides a strategic framework for schools to reduce students' cognitive load in learning programming syntax, making the introduction to coding more effective, enjoyable, and relevant for vocational education.